Melampaui Tradisi: Menata Ulang Efisiensi Layanan Makanan Melalui Sistem Cook & Chill di Dapur Pusat ISMAYA Group - Dahlan, Zulkarnaini; Budi Setiawan (PT Wahana Global Education, 2025)
The food service industry faces challenges in maintaining operational efficiency, quality consistency, and cost control on a large scale. The cook and chill system is an innovation that offers solutions through food processing, rapid chilling, storage, and regeneration before serving. This study aims to analyse the implementation of cook and chill in the ISMAYA Group's central kitchen as a strategy to enhance efficiency and competitiveness. The research method uses a case study approach by combining secondary data from academic literature and primary data from field observations and interviews with operational managers. The results show that cook and chill can improve preparation time efficiency at outlets, reduce labour costs, and enhance consistency in taste and food presentation. The main challenges include high initial investment for equipment and the ongoing need for human resource training. Practical implications of this research include the need for change management strategies, the use of IoT-based temperature monitoring technology, and optimization of eco-friendly logistics. This study concludes that cook and chill is not only a technical strategy but also a managerial tool relevant to addressing the dynamics of the modern restaurant industry in Indonesia.